Influence of weather parameters on conidia formation in powdery mildew of grape - M.C. VARSHNEYA; J.D. PATIL, S.B. CHAVAN, S.V. KHANDGE (Indian Phytopathology, 2002)
The role of temperature and relative humidity on spore formation of Uncinula necator (Schw.) Burr. causing powdery mildew of grape (Vitis vinifera L.) was studied under field conditions during post-monsoon season of 1990-91. Five polythene compartments, each consisting of nine vines, were erected and irrigated at an interval of 4, 8, 12, 16 and 20 days in order to create varying microclimatic conditions, the temperature and relative humidity within the canopy of vine were continuously recorded with the help of thermocouples and thermocouple psychrometer respectively. The conidia of the fungus counted with haemocytometer indicated the rapid spore production and disease multiplication during December and January when the climate was cool and humid a compared to the climate in November and February. The temperature in the range of 12.2 to 30.1Â°C and relative humidity greater than 57.4 per cent favoured the spore production of U. necator. Below 8.8Â°C the conidia production was hampered, however, theycan survive.